PRODUCCIÓN AUTOMATIZADA DE CIRCUITOS ELECTRÓNICOS APLICADOS A LA ELECTROMEDICINA (Journal on studies and research of academic knowledge, 2017)
The following document describes the development of a mechanical / electronic prototype for the milling, drilling and assembly of printed circuit boards or Printed circuit boards (PCB). The work arises from the need to automate the production processes of electronic circuit boards applicable to small solutions for electromedicine and thus take a step forward in the manufacture of safer printed circuit boards, seeking to advance the development process manual and the use of chemicals for production. The safety requirements of electronic Boards o PCB in the electromedicine are high depending on the device to which it is applied and its importance to sustain human life. The machine works by means of computer numerical control (CNC). The most indicated mechanism for the construction and assembly of electronic circuits among the different mechanical forms implemented by this type of machines was analyzed. The components that make up the hardware were integrated with a control software called Universal Gcode sender (UGS). Functionality tests were performed to calibrate the prototype, yielding satisfactory results in terms of precision in the milling, congenializing the speed and depth of the draft. Two types of structures were tested and different conclusions and recommendations were generated for both types of designs.
Keywords: CNC; Electromedicine; UGS; PCB